(untitled) (UCC Student Medical Journal, 2026)
Cardiac fibrosis is a major driver of heart failure, with complex mechanisms contributing to its progression. One such contributor is latent transforming growth factor-beta binding protein-2 (LTBP2), a protein significantly upregulated in fibrotic tissues. Unlike other TGF-beta binding proteins, LTBP2 does not bind to TGF-beta, and its role in cardiac fibrosis is largely unexplored. However, LTBP2 is involved in key profibrotic signaling pathways, including those related to TGF-beta1, fibroblast growth factor-2 (FGF-2), caspase-3, and NF-kB, all of which are potential therapeutic targets. Notably, NF-kB signaling activation through LTBP2 in fibrosis progression has been identified as an important mechanism that warrants further investigation. In addition to its role in cell signaling, LTBP2 is essential for maintaining microfibril structural integrity, particularly in tissues such as the eye. However, the specific contributions of LTBP2 and microfibrils to cardiac fibrosis remain to be fully elucidated. Furthermore, LTBP2’s early-stage upregulation and its presence in circulating serum highlight its potential as a biomarker for fibrotic diseases. Studies in pulmonary fibrosis and other organ systems have demonstrated that serum LTBP2 levels correlate with fibrosis progression and the differentiation of fibroblasts to myofibroblasts. These findings suggest that LTBP2 may serve as an early indicator of cardiac fibrosis. Overall, the investigation of LTBP2’s role in cardiac fibrosis is crucial for understanding its therapeutic potential and for identifying new strategies to promote reparative fibrosis and prevent the progression to heart failure.